MATHEMATICS
MIDDLE SCHOOL

Answer: You can use ten blocks to find 2.16/3 by using 7 base ten blocks and two base one blocks

HIGH SCHOOL

5/8 of an inch in fraction form and decimal dorm

5/8 inches

Fraction form: 5/8

Decimal form: 0.625

Fraction form: 5/8

Decimal form: 0.625

MIDDLE SCHOOL

Brad puts an equal amount of money in his savings account once a month. He started with $25. The next month, he had $35 in his account. Two months after that, he had $55 in his account. How much money will Brad have in his account after 6 months?

He adds $10 a month. He starts with $25. $10 times 6 months equals $60. $25+$60=$85

Hope I helped

Hope I helped

First, find how much money he puts into his account each month.

Month 1 - starting amount = 35 - 25 = 10.

Using this information, you can write the equation:

t = total amount m = number of months after start

t = 25 + 10m

You can check whether or not this equation is correct by plugging in the other information given.

55 = 25 + 10(3)

55 = 25 + 30

55 = 55

The equation is correct.

Now, you can plug in 6 for the number of months.

t = 25 + 10m

t = 25 + 10(6)

t = 25 + 60

t = 85

Brad will have $85 in his account after six months.

Month 1 - starting amount = 35 - 25 = 10.

Using this information, you can write the equation:

t = total amount m = number of months after start

t = 25 + 10m

You can check whether or not this equation is correct by plugging in the other information given.

55 = 25 + 10(3)

55 = 25 + 30

55 = 55

The equation is correct.

Now, you can plug in 6 for the number of months.

t = 25 + 10m

t = 25 + 10(6)

t = 25 + 60

t = 85

Brad will have $85 in his account after six months.

MIDDLE SCHOOL

Here are three sequences of numbers. The first three numbers are related by a specific pattern that produces the fourth number. Find out what the rule is and find the missing number. 4 3 6 = 8

3 5 5 = 3

6 3 3 = ?

Multiply the third number by the second, then multiply this result by the first.

6/3 = 2 ==> 4*2 = 8

5/5 = 1 ==> 3*1 = 3

3/3 = 1 ==> 6*1 = 6